Nivel de comercialización de la Bananera La Tello en la Parroquia Guare, periodo 2023. - Cubero Añasco, Ángeles Jamali (2024)
This case study focuses on La Tello Banana Company, located in the parish of Guare, province of Los Ríos, Ecuador, with the aim of analyzing the company's level of commercialization during the year 2023. Despite its solid track record in banana production and export, La Tello faces serious challenges that restrict its ability to effectively distribute its products and compete in local, national and international markets. The research seeks to identify the root causes of these problems and evaluate the company's performance. The method of methodological approximation was applied, which combines the compilation of qualitative and quantitative data. In the qualitative section, a nine-quadrant SWOT matrix was executed and an interview was conducted with the organization's sales manager to determine the effectiveness of the marketing tactics applied in the banana plantation. On the other hand, in the quantitative technique, a survey was conducted with the entity's employees to understand their perspective on the distribution processes and other pertinent characteristics. Through the information obtained, multiple deficiencies in the sale of the fruit were identified, deficiencies such as weak commercial associations, lack of effectiveness in making marketing decisions, subordination to traditional methods, problems in the timely supply of resources that cause operational interruptions. In response to these shortcomings, alternatives were suggested to optimize the marketing of the La Tello banana company, which includes product improvement, innovation in marketing methods, and consolidation of commercial alliances. These proposals are aimed at intensifying competitiveness and sustainability in a competitive commercial environment, stimulating its growth and expansion.